Context Matters: Hawaiian Monk Seals Switch Between Feeding Strategies Depending on Ecological Context. (29th July 2020) - Kienle, Sarah S; Powers, Jezebel; Kendall, Traci; Richter, Beau; Castle, Leann; Lentes, Gwen; Costa, Daniel; Mehta, Rita S
Synopsis: The ability to expand the behavioral repertoire past seemingly rigid morphological features enables animals to succeed in a variety of ecological contexts. The integration of morphology, performance, and behavior produces diverse animal feeding strategies. These different strategies reflect trade-offs between specialization, prey choice, and energetic expenditure, which have important consequences for understanding individual and population-level flexibility in response to environmental change. Here we examined the feeding strategies used by the Hawaiian monk seal ( Neomonachus schauinslandi ), an endangered marine predator. We tested how Hawaiian monk seal feeding strategies change in response to ecological context, specifically prey size and prey location at different depths. Seven captive Hawaiian monk seals were fed five prey types across a continuum of sizes, and prey were presented at three depths to represent surface, pelagic, and benthic feeding. Hawaiian monk seals used suction feeding and biting strategies, and these strategies were associated with significant differences in behavior and kinematic performance. Hawaiian monk seals used suction feeding most frequently when targeting small to medium prey (0–79% of the seal's head length) but switched to biting when consuming large prey (>80% of the seal's head length). These results demonstrate that prey size drives the transition between suction feeding and biting strategies. Seals also switched strategies based on prey position in the water column, primarily using suction feeding when prey were benthic and pelagic, and biting when prey were at the water's surface. Overall, suction feeding was three to five times faster than biting, required a smaller gape, and used fewer jaw movements, allowing seals to quickly consume numerous small to medium sized prey. In contrast, biting was slower but resulted in the ability to target larger, potentially more energy rich prey. Our results show that Hawaiian monk seals exhibit flexibility in their use of different feeding strategies, which likely facilitates increased foraging success when feeding in spatially and temporally dynamic marine environments.